Renewable Castor‐Oil‐based Waterborne Polyurethane Networks: Simultaneously Showing High Strength, Self‐Healing, Processability and Tunable Multishape Memory - Zhang, Chaoqun; Liang, Haiyan; Liang, Dunsheng; Lin, Zirun; Chen, Qian; Feng, Pengju; Wang, Qingwen (Angewandte Chemie International Edition, 2021)
Materials with multifunctionality or multiresponsiveness, especially polymers derived from green, renewable precursors, have recently attracted significant attention resulting from their technological impact. Nowadays, vegetable‐oil‐based waterborne polyurethanes (WPUs) are widely used in various fields, while strategies for simultaneous realization of their self‐healing, reprocessing, shape memory as well as high mechanical properties are still highly anticipated. We report development of a multifunctional castor‐oil‐based waterborne polyurethane with high strength using controlled amounts of dithiodiphenylamine. The polymer networks possessed high tensile strength up to 38 MPa as well as excellent self‐healing efficiency. Moreover, the WPU film exhibited a maximum recovery of 100 % of the original mechanical properties after reprocessing four times. The broad glass‐transition temperature of the samples endowed the films with a versatile shape‐memory effect, including a dual‐to‐quadruple shape‐memory effect. A castor‐oil‐based waterborne polyurethane (WPU) with high strength was developed. The PU networks demonstrated high tensile strength up to 38 MPa, excellent self‐healing with a tensile strength of 100 %, and a maximum recovery of 100 % of the original mechanical strength after reprocessing four times. The broad glass‐transition temperature of the samples endows the films with shape‐memory effects.